A SOCIAL ANALYSIS OF THE TRANSFORMATION AGENDA OF PRESIDENT GOODLUCK EBELE JONATHAN - Gyong, John Emmanuel (European Scientific Journal, ESJ, 2012)
There have been a number of visions and policies pursued by previous Heads of Government of Nigeria from Independence to the present democratic dispensation of President Goodluck Ebele Jonathan. President Goodluck Ebele Jonathan took oath of office on 29 May, 2011 amidst thunderous expectations of a new dawn, given the mountain of problems that characterized the nation. Realizing the high expectations of the citizens, the President promised Nigerians a policy package tagged the Transformation Agenda. This is a 5-year development plan 2011-2015, driven by a world class team of 28 technocrats under the Chairmanship of the President himself and the coordination of a renowned Economist in person of Dr. Ngozi Okonjo-Iweala. The Transformation Agenda itself is focused on three key areas which include strong, inclusive and non-inflationary growth; employment generation and poverty alleviation and value re-orientation of the citizenry. Using thirteen key sectors as the spring board, the President hopes to transform the whole economy of Nigeria. The strength of the Transformation Agenda lie in one, a well thought out policy document; two, a world class Economic Management Team to drive the process though; three a potential financial, human and political resource base; four, a growing maturity of major institutions of governance such as the National Assembly, the Judiciary, an electoral umpire and the Armed Forces; and five, the needlessness to „re-invent the wheel. as several strategic plans blue print are already in place. Nevertheless, there are a number of threats and challenges to the realization of the Transformation Agenda. These include, one, absence of good governance and accountability; two, ineffective public service; three, lack of synergy between political office holders and holders of public office; four, the incessant problem of insecurity; five, corruption; six, bankrupt leadership; and seven, a faulty development agenda that is currently driving the Transformation Agenda. In conclusion therefore, there is the need to take bold steps towards exploiting the maximum benefits of the opportunities and strengths of the Transformation Agenda, while simultaneously reducing, to the barest minimum, the threats and challenges facing it. Most importantly, some fundamental measures need to be taken in the thinking and actions of the leadership of the country. Finally, there is the need for a radical development strategy that will guarantee inclusiveness as opposed to exclusiveness in the Governance of the Transformation Agenda to be in firm place.